Role of Technical Institutes, Industries and Professional Bodies in Continuing Education - Yasin, Masooda (Journal of Engineering Education Transformations, 1995)
The paper highlights the need for Continuing Education in general and for Technical Education in particular with a special focus at Polytechnic level and the role played by organizations like Technical Institutes, Professional Bodies and Industries. The paper further detail out that what resources can be pulled from these organizations and what sort of approach to be adopted in conducting Continuing Education Activities With Optimum Utilization of Resources.